The Minorities of Chinese Philosophy: Ideology and Identity in the Academic Discipline of "Ethnic Minority Philosophy". (May 2022) - Van den Stock, Ady
The academic discipline of "ethnic minority philosophy, " which emerged at the beginning of the 1980s in the People's Republic of China, has thus far remained virtually unstudied in Western-language scholarship. The aim of this article is to place the genesis and development of this little-known discipline against the wider background of modern Chinese scholarly and political discourses on the interrelated issues of national, ethnic, cultural, philosophical, and religious identity. In doing so, this article analyzes what I call the "hierarchical inclusion" of minority traditions into the history of Chinese philosophy, the perceived proximity between ethnic minority philosophies and "primitive religion, " and the role of the problematic concept of "culture" in the reinvention of minoritarian traditions of thought as philosophy.